Mammalian Taste Cells Express Functional Olfactory Receptors - Malik, Bilal (Chem Senses, 2019)
The peripheral taste and olfactory systems in mammals are separate and independent sensory systems. In the current model of chemosensation, gustatory, and olfactory receptors are genetically divergent families expressed in anatomically distinct locations that project to disparate downstream targets. Although information from the 2 sensory systems merges to form the perception of flavor, the first cross talk is thought to occur centrally, in the insular cortex. Recent studies have shown that gustatory and olfactory receptors are expressed throughout the body and serve as chemical sensors in multiple tissues. Olfactory receptor cDNA has been detected in the tongue, yet the presence of physiologically functional olfactory receptors in taste cells has not yet been demonstrated. Here we report that olfactory receptors are functionally expressed in taste papillae. We found expression of olfactory receptors in the taste papillae of green fluorescent protein-expressing transgenic mice and, using immunocytochemistry and real-time quantitative polymerase chain reaction experiments, the presence of olfactory signal transduction molecules and olfactory receptors in cultured human fungiform taste papilla (HBO) cells. Both HBO cells and mouse taste papilla cells responded to odorants. Knockdown of adenylyl cyclase mRNA by specific small inhibitory RNA and pharmacological block of adenylyl cyclase eliminated these responses, leading us to hypothesize that the gustatory system may receive olfactory information in the periphery. These results provide the first direct evidence of the presence of functional olfactory receptors in mammalian taste cells. Our results also demonstrate that the initial integration of gustatory and olfactory information may occur as early as the taste receptor cells.